Ideologi dalam Bahasa Perempuan terhadap Dugaan Pelecehan Seksual di Ajang Kontes Kecantikan: Analisis Wacana Kritis - Ardhianti, Mimas (Deskripsi Bahasa, 2024)
The case of sexual harassment involving women as victims can be seen from the news in the news media lately is quite shocking, a number of female finalists of Miss Universe Indonesia 2023 came to Polda Metro Jaya to file a report about the alleged harassment of her without clothes. The purpose of this research is to uncover ideology in women's language towards alleged sexual harassment in beauty pageants. In accordance with these objectives, qualitative descriptive is used as an approach to this research. The data of this research is in the form of lingual features obtained during online netnographic observation of participants on Instagram belonging to the finalists of Miss Universe Indonesia (MUID) 2023, peagent portal, and Yayasan Puteri Indonesia. The data were collected using Kozinets' (2010) netnography procedure, which is a form of adoption of ethnographic techniques in the realm of cyberspace. Online netnography observations in this study were conducted through device screens and laptops observing the status uploaded on instgram accounts. To analyze the data, Fairclough's Critical Discourse Analysis model is used, namely description, interpretation, and explanation. The findings of this research are the existence of ideological manifestations, namely (1) ideology 1: "fighting for women's rights in beauty contests", (2) ideology II: "feeling what harassed women feel", (3) ideology III: "trusting the law in upholding justice for victims", and (4) ideology IV: "erasing the negative stigma of society towards beauty pageants". The conclusion of this study is that women choose and utilize certain lingual forms and ignore other forms, namely institutional processes and sociocultural processes.